2021
DOI: 10.1016/j.crphar.2021.100062
|View full text |Cite
|
Sign up to set email alerts
|

Can the application of graphene oxide contribute to the fight against COVID-19? Antiviral activity, diagnosis and prevention

Abstract: COVID-19 is an infectious disease that affects the respiratory system and is caused by the novel coronavirus SARS-CoV-2. It was first reported in Wuhan, China, on December 31, 2019, and has affected the entire world. This pandemic has caused serious health, economic and social problems. In this situation, the only solution to combat COVID-19 is to accelerate the development of antiviral drugs and vaccines to mitigate the virus and develop better antiviral methods and excellent diagnostic and prevention techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The interaction of graphene and viruses constitutes a distinct addition to the potential successful applications of COVID-19, where Di et al prepared graphene and antibody-coupled panels respectively that can rapidly detect target virus proteins and thus can be a very useful population screening group [12] . In 2012, the effect of graphene on viruses was reported, whereby it revealed that graphene had a good ability to inhibit viruses.…”
Section: Interaction Of Graphene and Its Derivatives-based Materials ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of graphene and viruses constitutes a distinct addition to the potential successful applications of COVID-19, where Di et al prepared graphene and antibody-coupled panels respectively that can rapidly detect target virus proteins and thus can be a very useful population screening group [12] . In 2012, the effect of graphene on viruses was reported, whereby it revealed that graphene had a good ability to inhibit viruses.…”
Section: Interaction Of Graphene and Its Derivatives-based Materials ...mentioning
confidence: 99%
“… [54] . Graphene oxide has shown promise in many key areas to fend viruses such as H9N2, Pseudorabies and enteric EV71 due to its ability to grab on to viruses and disable it [12] . An explanation to its catching capabilities, GBNPs have sharp edges at which viruses get caught in and is dismantled.…”
Section: Relevance Of Graphene and Its Materials In Battling The Covi...mentioning
confidence: 99%
“…A key part of the material is the functional groups of activated graphene oxide, which improves the filtration process (Chung et al, 2021;Rhazouani et al, 2020;Song et al, 2015). In contrast to pristine graphene, graphene oxide and reduced graphene oxide interact more rapidly with the outer lipoprotein layer of bacteria and viruses as they pass through the different layers of the face mask.…”
Section: Air Filtration By Graphene Face Maskmentioning
confidence: 99%
“…Recently, owing to the COVID-19 pandemic, many research groups have determined that SARS-CoV-2 is transmitted by fine droplets or aerosol particles containing infectious viruses, , and research on aerosol protection with membranes in protective equipment is being actively conducted. Although extensive studies have been performed on protective membranes by adding various materials such as graphene, , graphene oxide, , metal–organic frameworks, and metal oxides, , the vast majority of such studies have been focused on water-vapor-permeable membranes instead of air-permeable membranes. For example, graphene-oxide-added membranes are being actively studied for gas separation , and for inhibiting the attachment of the virus. , However, it is typically used as a semipermeable membrane and exhibits poor air permeability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, graphene-oxide-added membranes are being actively studied for gas separation 19,20 and for inhibiting the attachment of the virus. 21,22 However, it is typically used as a semipermeable membrane and exhibits poor air permeability. With the rapid growth of the membrane-based gas separation technology, protection from CWAs using membranes has emerged as a feasible strategy.…”
Section: Introductionmentioning
confidence: 99%